Discussion of The LIFO/FIFO Choice: An Asymmetric Information Approach - Fellingham, John (Journal of Accounting Research, 1988)
John Fellingham, Discussion of The LIFO/FIFO Choice: An Asymmetric Information Approach, Journal of Accounting Research, Vol. 26, Studies on Management's Ability and Incentives to Affect the Timing and Magnitude of Accounting Accruals (1988), pp. 59-62